2021
DOI: 10.3389/fonc.2021.624759
|View full text |Cite
|
Sign up to set email alerts
|

Use of Salmonella Bacteria in Cancer Therapy: Direct, Drug Delivery and Combination Approaches

Abstract: Over the years, conventional cancer treatments, such as chemotherapy with only a limited specificity for tumors, have undergone significant improvement. Moreover, newer therapies such as immunotherapy have undergone a revolution to stimulate the innate as well as adaptive immune responses against the tumor. However, it has been found that tumors can be selectively colonized by certain bacteria, where they can proliferate, and exert direct oncolytic effects as well as stimulating the immune system. Bacterial-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 138 publications
0
28
0
Order By: Relevance
“…Compared with monoclonal antibodies and small molecule inhibitors, the use of siRNA to treat tumors requires an effective delivery system. In addition to viral vectors, recent studies have shown that a variety of bacteria can be used as carriers, among which attenuated Salmonella is the most widely studied and applied ( 49 , 50 ). As a vehicle, attenuated Salmonella can carry small hairpin RNA (shRNA ) to a variety of tumor sites, including lung cancer, breast cancer, gastric cancer and prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with monoclonal antibodies and small molecule inhibitors, the use of siRNA to treat tumors requires an effective delivery system. In addition to viral vectors, recent studies have shown that a variety of bacteria can be used as carriers, among which attenuated Salmonella is the most widely studied and applied ( 49 , 50 ). As a vehicle, attenuated Salmonella can carry small hairpin RNA (shRNA ) to a variety of tumor sites, including lung cancer, breast cancer, gastric cancer and prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical data showed a high percentage of bacteria maintained in blood after administration for longer period. Other than that, the limited cytotoxic properties of bacteria requiring conjugation with chemotherapeutic agents as well as the risk of mutation due to genetic modification are also obstacles that need to be overcome to utilise bacteria as a potential therapy in cancer patients ( 5 , 103 , 104 ). On the other hand, BGs has its limitation as a delivery system.…”
Section: The Obstacle Of Bacterial Therapymentioning
confidence: 99%
“…Modifications regarding synthesis and delivery of anticancer payloads by bacteria are also worth briefly noting. The list of therapeutic payloads continues to grow, with focus placed largely on incorporation or secretion of cytokines, TAA, immune modulators, prodrugs, gene silencers or transport effectors [202,203] (Figure 4). For example, Salmonella avoids detection through use of a modified vacuole, the salmonella-containing vacuole (SCV), allowing time to accomplish replication-which could be exploited as a platform for either continuous drug delivery or to reach therapeutic levels higher than the initial dosage [204,205].…”
Section: The Optimization Of Bacteria-mediated Oncotherapeutic Payloadsmentioning
confidence: 99%